Manganese PNP-pincer catalyzed isomerization of allylic/homo-allylic alcohols to ketones – activity, selectivity, efficiency. Issue 22 (18th October 2019) - Xia, Tian; Spiegelberg, Brian; Wei, Zhihong; Jiao, Haijun; Tin, Sergey; Hinze, Sandra; de Vries, Johannes G.
Abstract : Manganese PNP pincer complexes are excellent catalysts for the isomerization of allylic alcohols to the ketones. The reaction proceeds via a dehydrogenation/hydrogenation mechanism as shown by DFT calculations and deuterium labelling. Abstract : We report the first manganese catalyzed isomerization of allylic alcohols to produce the corresponding carbonyl compounds. The ligand plays a decisive role in the efficiency of this reaction. Very high conversions could be obtained using a solvent-free reaction system. A detailed DFT study reveals a self-dehydrogenation/hydrogenation reaction mechanism which was verified by the isolation of the α, β-unsaturated ketone as intermediate and a deuterium labeling experiment. It also provided a rationale for the observed selectivity and the higher efficiency of phenyl over isopropyl substitution.